Promoting reconciliation through research collaboration between Xaaynangaa Naay and Northern Health Authority: Beginning the dialogue - Hartney, Elizabeth; Gladstone, Susan (Royal Roads University, 2019)
This project was supported by the Government of Canada through a SSHRC Connection Grant. The authors acknowledge the contributions of Lauren Brown, Director, Janet Rigg, Mental Health and Wellness Counsellor, and Waneeta Richardson, First Nations Health Authority, in leading the background work on which this project is based. We also acknowledge Elders Diane Brown, Betty Richardson, Isabel Brillon, Kay Watson, and Pete Thompson, and Cindy Williams, community member, in contributing to the dialogue that led to this project. A previous Planning and Dissemination Grant from the CIHR enabled the project plan to be developed, which formed the basis of the proposal for this project. This project was supported by the Government of Canada through a SSHRC Connection Grant, and builds on a previous project supported by a CIHR Planning and Dissemination Grant. The first project was focused on developing Indigenous leadership through facilitating collaboration between First Nations and Indigenous peoples and regional health authorities in British Columbia. A detailed report is available (Hartney, 2018). Through the previous project, and earlier work conducted by members of the project team in Haida Gwaii, this project was conceived. A series of Elders dinners had been held in the community, to facilitate the leadership of Elders in mental health services in the Skidegate community. This project expands on the successful approach used previously, by bringing together Elders from the ten clans of the Haida Nation, with leadership from Northern Heath Authority, with the intention to build trusting relationships. The project will support Indigenous talent and research careers by employing a knowledge keeper from within the community, and engaging with Elders as project participants, thereby demonstrating their strengths as advisors to the health authority. The data collection method used will be talking circles. The work will further develop the Indigenous research career of the Health Director, Lauren Brown, building on her ...